Asian Voices in Christian Theology - Anderson, Gerald H. (Maryknoll Orbis Books, 1976)
To theological maturity / Tongshik Ryu -- Japan : where theology seeks to integrate text and context / Yoshinibo Kumazawa.
Keywords: Theology, Doctrinal -- Asia -- History. Theology, Doctrinal. Asia. Contextuele theologie. Christentum Asien Doctrinal theology -- Asia -- History -- Addresses, essays, lectures